Vibration-based condition monitoring : industrial, aerospace and automotive applications - Randall, Robert Bond (Chichester, West Sussex ; Hoboken, NJ : Wiley, 2011)
"Randall provides a comprehensive survey of the applications of vibration analysis to the condition monitoring of machines, reflecting the natural progression of these systems by presenting the fundamental material and then moving onto detection, diagnosis and prognosis"--
1. Introduction and background -- Maintenance strategies -- Condition monitoring methods -- Types and benefits of vibration analysis -- Vibration transducers -- Torsional vibration transducers -- Condition monitoring: the basic problem -- 2. Vibration signals from rotating and reciprocating machines -- Signal classification -- Signals generated by rotating machines -- Signals generated by reciprocating machines -- 3. Basic signal processing techniques -- Probability distribution and density -- Fourier analysis -- Hilbert transform and demodulation -- Cepstrum analysis -- Digital filtering -- Deterministic/random signal separation -- Time-frequency analysis -- Cyclostationary analysis and spectral correlation -- 4. Fault detection -- Rotating machines -- Reciprocating machines -- 5. Diagnostic techniques -- Harmonic and sideband cursors -- Minimum entropy deconvolution -- Spectral kurtosis and kurtogram -- Gear diagnostics -- Rolling element bearing diagnostics -- Reciprocating machine and IC engine diagnostics -- 6. Fault trending and prognostics -- Trend analysis -- Determination of spall size in bearings -- Advanced prognostics -- App.: Exercises and tutorial questions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Vibration -- Testing; Nondestructive testing; Vibration -- Measurement; TECHNOLOGY & ENGINEERING -- Machinery; Nondestructive testing; Vibration -- Measurement; Vibration -- Testing; Electronic books